Reinforced concrete wall as protection against accidental explosions in the petrochemical industry - Ambrosini, Ricardo Daniel (2009)
In this paper the study of a reinforced concrete wall used as protection against accidental explosions in the petrochemical industry is presented. Many alternatives of accidental scenarios and sizes of the wall are analyzed and discussed. Two main types of events are considered, both related to vessel bursts: Pressure vessel bursts and BLEVE. The liberated energy from the explosion was calculated following procedures firmly established in the practice and the effects over the structures and the reinforced concrete wall were calculated by using a CFD tool. The results obtained show that the designed wall reduces the values of the peak overpressure and impulse and, as a result, the damage levels to be expected. It was also proved that a reinforced concrete wall can withstand the blast load for the considered events and levels of pressure and impulse, with minor damage and protect the buildings.